Diagnostic and Therapeutic Challenges of Catatonia in an Adolescent With High Functioning Autism Spectrum Disorder: A Case Report - Traverso, Annalisa; Ancora, Caterina; Zanato, Silvia; Raffagnato, Alessia; Gatta, Michela (Frontiers in Psychiatry, 2021)
Catatonia is a psychomotor syndrome with specific clusters of speech, behavioral and motor features. Although potentially life-threatening, especially in its malignant form accompanied with autonomic dysregulation and medical complications, it is a treatable condition, when promptly identified. For a long time catatonia was considered a marker of schizophrenia, thus limiting the possibility of diagnosis and treatment. Due to growing awareness and studies on the subject, it is now known that catatonia can occur in the context of a number of diseases, including psychotic, affective and neurodevelopmental disorders. In recent years, there’s been a renewed interest in the recognition and definition of catatonia in neurodevelopmental disorders, such as Autism Spectrum Disorder (ASD), where the differential diagnosis poses great challenges, given the considerable overlapping of signs and symptoms between the conditions. We present the case of a 15 year old boy with High Functioning ASD with a sudden onset of severe catatonic symptoms and the co-existence of psychotic symptoms, whose complex clinical course raises many questions on the differentiation and relation of said disorders.